Bending potential as an important factor for the structure of monomolecular thiolate layers on GaAs substrates - Lu, Hao; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry letters, 2013)
The presence of a substrate-dependent binding geometry at the anchoring group and its energetics (bending potential) are known to be important in determining the lateral density and structure of self-assembled monolayers (SAMs) of thiolates and selenolates on coinage metal substrates. Here we show that on the technologically important GaAs(001) surface a bending potential exists for thiolate adlayers as well. For this, we used a series of terphenyl-substituted alkanethiols, C6H5(C6H4)2(CH2)nSH (TPn, n = 0-6), as a suitable model system. The bending potential plays a dominant role in the balance of the structure-building interactions in the TPn SAMs on GaAs, resulting in a persistent, “odd-even” variation of molecular orientation and packing density in these monolayers as a function of the parity of n. This observation should necessarily be considered for the design of future, functional SAMs on GaAs(001).
Gesehen am 08.06.2021